Cancers in Australia attributable to exposure to solar ultraviolet radiation and prevented by regular sunscreen use. (October 2015) - Olsen, Catherine M.; Wilson, Louise F.; Green, Adele C.; Bain, Christopher J.; Fritschi, Lin; Neale, Rachel E.; Whiteman, David C.
Abstract Objectives: To estimate the proportion and numbers of cancers occurring in Australia attributable to solar ultraviolet radiation (UVR) and the proportion and numbers prevented by regular sun protection factor (SPF) 15+ sunscreen use. Methods: We estimated the population attributable fraction (PAF) and numbers of melanomas and keratinocyte cancers (i.e. basal cell carcinomas and squamous cell carcinomas) due to exposure to ambient UVR resulting from residing in Australia versus residing in the UK (for melanoma) or Scandinavia (for keratinocyte cancers). We also estimated the prevented fraction (PF): the proportion of cancers that would have occurred but were likely prevented by regular sunscreen use. Results: An estimated 7, 220 melanomas (PAF 63%) and essentially all keratinocyte cancers occurring in Australia were attributable to high ambient UVR levels in Australia. We estimated that regular sunscreen use prevented around 14, 190 (PF 9.3%) and 1, 730 (PF 14%) people from developing SCC and melanoma, respectively. Conclusions: Although our approach was conservative, a high proportion of skin cancers in Australia are attributable to high ambient levels of UVR. Prevailing levels of sunscreen use probably reduced skin cancer incidence by 10–15%. Implications: Most skin cancers are preventable. Sunscreen should be a component of a comprehensive sun protection strategy.